Colibacillosis in poultry: A disease overview and the new perspectives for its control and prevention - KOUTSIANOS, D.; ATHANASIOU, L.; MOSSIALOS, D.; KOUTOULIS, K. C. (Journal of the Hellenic Veterinary Medical Society, 2021)
Escherichia coli (E.coli) is a common bacterium that can be naturally found in the intestinal tract of birds and as a result in their environment. However, it can cause clinical disease called colibacillosis which is regarded as one of the most common and important diseases in poultry. Strains of E.coli that have the ability to cause clinical disease are described as Avian Pathogenic Escherichia Coli (APEC). Colibacillosis can affect birds of all ages and different types of poultry production including broiler and commercial layers and breeders. The ability of E.coli to cause colibacillosis is not always the same; that is why its role as primary or secondary pathogen triggered by various predisposing factors is contradictory and differs from case to case. Antibiotics have been used as the main tool against colibacillosis for many decades. However, the emergence of increased antibiotic resistance has posed the need of alternative treatment to colibacillosis as well as emphasizing on preventive measures to avoid disease. Τhe scope of this article is to assess recent scientific literature data on avian colibacillosis emphasizing on disease characteristics and recent data on prevention and control of the disease.